Measurements Of High Frequency Electromagnetic Waves In Center Of Mus - Taha Etem; Teymuraz ABBASOV (International Journal of Applied Methods in Electronics and Computers, 2016)
All electrically powered devices cause electromagnetic wave exposure on human body and we use them nearly every moment in a day. Mobile phones, computers, televisions, hair dryers, lighting systems, etc. they all use electricity and naturally radiate electromagnetic waves. Effects of electromagnetic waves are not clear but international organizations define limit values depending on epidemiological studies in this field. In this study we measure high frequency electromagnetic waves in city center of Mus. Measurements are made at mobile phone frequencies and results compared with limit values. All measurement techniques and limit values are appropriate with Information and Communication Technologies Authority (ICTA) standards. Measurement points are selected according to population density in city center